TGFβ2 is a Prognostic Biomarker for Gastric Cancer and is Associated With Methylation and Immunotherapy Responses - Han, Bangling; Fang, Tianyi; Wang, Yimin; Zhang, Yongle; Xue, Yingwei (Frontiers in Genetics, 2022)
TGFβ signaling plays a key role in cancer progression and by shaping tumor architecture and inhibiting the anti-tumor activity of immune cells. It was reported that high expression of TGFβ can promote the invasion and metastasis of cancer cells in a variety of tumors. However, there are few studies on TGFβ2 and its methylation in gastric cancer. We analyzed the Harbin Medical University Cancer Hospital (HMUCH) sequencing data and used public data to explore the potential function and prognostic value of TGFβ2 and its methylation in gastric cancer. In this study, we used the ssGSEA algorithm to quantify 23 methylation sites related to TGFβ2. Survival analysis showed that high expression of TGFβ2 and hypomethylation levels of TGFβ2 were negative factors in the prognosis of gastric cancer. Functional enrichment analysis of methylation revealed that methylation of different TGFβ2 methylation scores was mainly involved in energy metabolism, extracellular matrix formation and cell cycle regulation. In the gastric cancer microenvironment TGFβ2 was associated with high levels of multiple immune cell infiltration and cytokine expression, and high TGFβ2 expression was significantly and positively correlated with stemness markers, stromalscore and EMT. Gene set enrichment analysis also revealed an important role of TGFβ2 in promoting EMT. In addition, we discussed the relationship between TGFβ2 and immunotherapy. The expression of PD-1, PD-L1 and CTLA-4 was elevated in the TGFβ2 high expression group. Also when TGFβ2 was highly expressed, the responsiveness of immune checkpoint blockade (ICB) was significantly enhanced. This indicates that TGFβ2 may become an indicator for predicting the efficacy of immunosuppressive agents and a potential target for immunotherapy.